PROCESSED PRODUCT DEVELOPMENT OF ETHNIC GROUPS IN THE NORTHERN ECONOMIC CORRIDOR TO PROMOTE DISTRIBUTION THROUGH ONLINE CHANNELS BY APPLYING INFORMATION SYSTEMS OF COMMUNITY FINANCIAL INSTITUTIONS - KAMOLTHIP, Kamchai; PONGWIRITTHON, KAJORNATTHAPOL (Asian Administration and Management Review, 2023)
This research aims to develop processed products and utilization of value-added scraps from agricultural products and develop the information system of community financial institutions and access the satisfaction of the use of promoting the distribution through online channels of ethnic processed products. The results found that processed product development and utilization of value-added scraps from agricultural products of the vegetables and fruits group consists of the longest harvesting crops and is the main economic crop in the area, which applied “production wheel calendar of crop cycle and year cycle”. Guidelines to reduce the costs and create value-added agricultural products by obtaining the career skills of four courses, including sweet cape gooseberry biscuit, dried cape gooseberry, cape gooseberry jam, and cape gooseberry gummy. Also, the skill of value-added to the scraps from agricultural products by making fertilizer without turning the pile. For the online distribution channels by applying the information system of community financial institutions, the service for distributing products via the website which 85.45% presented the sale of products both in store and online. Success in the implementing overall satisfaction assessment of the information system is at the highest level which is to develop human beings and promote social responsibility and marketing, business, and marketing technology for sustainability in the future.